Pemanfaatan Media Sosial sebagai Strategi Komunikasi Teologi Misi (Program Studi Misiologi dan Komunikasi Kristen, 2024)
This study aims to describe the use of social media as a mission theology communication strategy. Using a qualitative approach with a descriptive method, because this method is a way to obtain data with specific purposes and uses, by utilizing printed and electronic books, journals, and websites. The results of the study describe that a communication strategy as planning, structuring and implementing an effective and efficient communication process is very important for communicating mission theology in the digital and post-humanism era. By utilizing social media while implementing the steps of a communication strategy, social media users can create messages related to mission theology, which can be conveyed and received easily by recipients. In the end mission theology will be considered important and not only for intellectuals. More than that, mission theology will become part of the work culture of Christians because social media becomes an intermediary for continuing to work or be creative, sharing and communicating, and a means for mutual collaboration.